SatEdge: Platform of Edge Cloud at Satellite and Scheduling Mechanism for Microservice Modules - Yanzhe Huang; Xing Zhang; Zechang Xu (IEEE Access, 2023)
Edge cloud at satellite (ECS) is a newly developed edge computing (EC) technology that uses EC services offered by satellites to support high reliability and seamless global coverage. Satellites assume the role of computing and storage nodes for edge clouds, while terrestrial control centers function as cloud centers. In this paper, we propose a novel system and software architecture for the ECS to improve the cloud management of satellite networks and increase the flexibility of satellite service provision at the edge. Then, we propose a platform for the ECS based on KubeEdge called SatEdge. SatEdge has many function modules to meet the needs of the satellite-terrestrial network (STN) such as high reliability, high flexibility, and low latency. On this platform, we designed a microservice scheduling algorithm called optimal microservice scheduling with adaptivity and mobility (OMS-AM). OMS-AM can schedule a globally optimal workflow for microservice modules on the satellites to minimize task processing latency, failed task rate, and energy consumption. Compared with our last work, OMS-AM reduces the task processing latency by 14% at most. Additionally, OMS-AM improves the mobility of the current scheduling method put forth in our previous study, which may help lower the task failure rate. Energy usage and the total normalized costs are additional indicators of the efficiency of the microservice architecture.